The Influence of Quality of Work Life on Job Satisfaction: (A Study of Government Sector Organizations in Surkhet District, Nepal) - Wagle, Debendra Kumar (Journal of Entrepreneurship & Management Studies, 2025)
Job satisfaction, which is closely linked to the quality of work life, plays a crucial role in enhancing employee well-being, motivation, productivity, and alignment with organizational goals. A positive work environment that supports employees’ needs fosters loyalty, reduces turnover, and contributes to long-term organizational success. This study investigates the influence of quality of work life on job satisfaction among government sector employees in Karnali Province, Nepal. It specifically explores how factors such as working environment, compensation and benefits, interpersonal relationships, and career development opportunities serve as predictors of job satisfaction. Data was collected from 396 government sector employees in the study area using a structured questionnaire administered through convenience sampling. Pearson’s correlation coefficient and regression analysis were applied to assess the relationships between the independent variables (working environment, compensation and benefits, interpersonal relationships, career development opportunities) and the dependent variable (job satisfaction) using SPSS version 25. The findings reveal that all four factorsworking environment, compensation and benefits, interpersonal relationships, and career development opportunitieshave a significant positive effect on job satisfaction. In conclusion, the study underscores the importance of the quality of work life in determining job satisfaction, emphasizing that factors such as a supportive work environment, adequate compensation, strong interpersonal relationships, and career growth opportunities are key to employee satisfaction. The implications of these findings suggest that government organizations in Surkhet district, and similar contexts, should prioritize improving these factors to enhance job satisfaction and improve overall organizational performance. This would lead to a more engaged, motivated, and loyal workforce, contributing to the long-term success of the organization.